2015
DOI: 10.1016/j.molonc.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

CCR9‐mediated signaling through β‐catenin and identification of a novel CCR9 antagonist

Abstract: Elevated levels of chemokine receptor CCR9 expression in solid tumors may contribute to poor patient prognosis. In this study, we characterized a novel CCR9-mediated pathway that promotes pancreatic cancer cell invasion and drug resistance, indicating that CCR9 may play a critical role in cancer progression through activation of β-catenin. We noted that the CCL25/CCR9 axis in pancreatic cancer cells induced the activation of β-catenin, which enhanced cell proliferation, invasion, and drug resistance. CCR9-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In mild to severe UC and CD, patients were shown to have increased numbers of CD14 + HLA-DR hi monocytes in the blood, and these cells express CCR9 and proinflammatory cytokine TNF-a [84]. The binding of CCL25 to CCR9 modulates b-catenin and leads to activation of the PI3K/ Akt signaling pathway [85]. CCR9 expresses on less activated/ mature plasmacytoid DCs and drives its migration into the gut [86].…”
Section: Ccr9 and Its Ligand Ccl25mentioning
confidence: 99%
“…In mild to severe UC and CD, patients were shown to have increased numbers of CD14 + HLA-DR hi monocytes in the blood, and these cells express CCR9 and proinflammatory cytokine TNF-a [84]. The binding of CCL25 to CCR9 modulates b-catenin and leads to activation of the PI3K/ Akt signaling pathway [85]. CCR9 expresses on less activated/ mature plasmacytoid DCs and drives its migration into the gut [86].…”
Section: Ccr9 and Its Ligand Ccl25mentioning
confidence: 99%
“…Overexpression of homeostatic chemokine receptors in tumor cells is linked to cancer progression, metastasis, and poor prognosis ( 22 ). Many reports describe a relevant role for the CCL25/CCR9 axis in cancer progression ( 26 , 30 ), in particular, CCR9 expression has been associated with leukemia aggressiveness ( 17 ), its aberrant expression has been detected in several solid tumors ( 14 , 15 , 17 30 , 40 ) and has been associated in organ selective metastasis of melanoma to small intestine ( 14 16 ), suggesting its potential as a target for cancer treatment. In this context, we have described the generation and characterization of mAb 91R, which inhibits CCR9 + -tumor growth on in vivo subcutaneous xenografts of human ALL in immunodeficient Rag2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 The receptors (cancer target proteins) used in the present study are highly expressed and closely involved at various stages of cell proliferations which eventually leads to propagation and invasion of cancer cells. [82][83][84][85] Docking was validated by redocking (Fig. 18).…”
Section: Apoptosis Study By Ao/eb Methodsmentioning
confidence: 99%
“…Docking of compounds 1 and 2 in the active sites of B-RAF kinase, PI3K-gamma receptors, CC chemokine receptor and EGFR kinase domain have been determined since these cancer targets proteins are over-expressed in multiple cancer types such as melanoma, colorectal, thyroid, non-small cell lung cancer, ovarian cancer, prostate cancer, pancreatic cancer, large B cell lymphoma, colon, brain, gastric, breast, bladder cancer and glioblastoma. [82][83][84][85] Moreover, these receptors are attractive targets for the diagnosis and treatment of various cancers. 83,84 The docking studies revealed that compound 2 docked in the active site of all the target proteins with signicant higher docking scores by virtue of hydrogen bonds (B-RAF kinase: CYS532, CYS532; CC chemokine receptor: PHE324, ARG323; EGFR kinase domain: ASP855, LYS745, ARG841 and PI3Kgamma receptors: ASP964, TYR867) and it was further validated by docking their respective standard inhibitors in the active site (Fig.…”
Section: Apoptosis Study By Ao/eb Methodsmentioning
confidence: 99%